Australasian Safari. - Australasian Safari ([Australia] : Australasian Safari, 2011)
"Australasian Safari is a partnership between Justin Hunt Management, a specialist motorsport event company, and Tourism Western Australia Australasian Safari, with its long history of competition throughout Australia and more recently Western Australia, is modernising to reflect our aims and targets to place this event at the forefront of motorsport competition within the region...Our aim stays the same "to provide the best, safest and most challenging long distance off-road race in the Asia Pacific region"."--About Us.
Title from title screen (viewed on 1 March 2016)
Mode of access: Available online. Address as at 01/03/16
Selected for archiving
Keywords: Motorsports -- Australia; Australian